Pelaksanaan Pendidikan Agama pada Sekolah-Sekolah di Kodia Malang - Kasiram, Moh. (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2001)
Religious education is one of theÂ more important elements in achieving the goal of national education in Indonesia. UUSPN No. 21 1989 and GBHN 1993 stated that religious education is compulsary for student in every level. This study tries to find out the implmentation of religious education inÂ Malang city. It is found out that (1) religious teachers are very serious in preparing the lesson; (2) the teachers use new methods in teaching religion i.e. experiments and problem solving; (3) the quality of teacher achievement again is very good in preparing teaching plans and implementing PBM in the classroom; (4) all schools are conducive to religious education, because all principals are the main supporters in religious activities in schools; and (5) the limitations of facilities, infrastructure and funds are the main obstacles.